Manipulation tactics and personality: results of Croatian twin study - Butković, Ana (2011)
Manipulation tactics represent different ways people try to influence others to do something for them. All people use them and they enable people to get what they need and want. Previous studies have shown that manipulation tactics covary significantly across data sources with different personality measures. In this study, using behavioral‐genetic design, we tested the hypothesis that covariation between manipulation tactics and personality is due to overlapping genetic factors. Data was collected via mail from 338 twin pairs (36 MZM, 49 DZM, 69 MZF, 70 DZF, 114 DZO), aged between 15 and 22 (M=18.6, SD=2.31). All participants filled in NEO‐FFI and manipulation tactics questionnaire from which scores for three types of manipulation tactics were obtained (indirect tactics for coercion or ITC, direct tactics or DT and indirect tactics for humoring or ITH), as well as a total sum score (TM). Significant phenotypic correlations between manipulation tactics and personality were, as expected, in .14‐.26 range. Univariate analysis showed that both manipulation tactics and personality are heritable. In bivariate analyses significant genetic correlations were obtained between manipulation tactics and neuroticism, extraversion, agreeableness and conscientiousness. Results indicate that 76‐100% of phenotypic correlations between manipulation tactics and personality are due to overlapping genetic factors.